PEMBUATAN MODIFIED CORN FLOUR (MOCOF) DARI JAGUNG LOKAL MELALUI PROSES FERMENTASI MENGGUNAKAN LARU Saccharomyces cerevisiae DANLARU Rhizopus oryzae - Ardi Kurniawan; Usman Pato; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Needs of flour in Indonesia reached 6.6 million tonnes in 2013. To reduce imports of wheat required the development of local food sources, including corn. Corn flour has several drawbacks such as the quality of the nutritional value is still low in comparison to wheat flour. To improve the quality and nutritional value of corn flour then necessary modifications. The manufacture of corn flour using the fermentation process is expected to alter its characteristics so as to extend the application of this starch as food products. This study used a Completely Randomized Design Experiment with 4 treatments and 4 repeats to obtain 16 experimental units. The data obtained were statistically analyzed using Analysis of Variance. If F count is greater than or equal to F table then continued with the test Duncan New Multiple Range Test at the 5% level. The results of this research show that using single and or combination of starters significantly affected all parameters. The best treatment to produce modified corn flour was P3 treatment using Saccharomyces cerevisiae 0,05% + Rhizopus oryzae 0,05% starters with rendement of 75.58%, moisture content 7.60%, pH 3.93, ash 0.43%, swelling power 10.47%, solubility 7.46%, fiber 0.30%, protein 9.84%, fat 3.61%, and carbohydrate contents of 78.51%. Keywords:  Fermentation, Saccharomyces cerevisiae, Rhizopus oryzae, modified corn flour and mocof